Analysis on generation Z's imaginary companions, gadget ownership, and their impact on consumer behavior - Putra, Komang Widhya Sedana (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2025)
This research explores the driving forces of Generation Z's consumption behavior in terms of gadget ownership, imaginary companions, and the inner child in the context of social media influences in an increasingly digital society. The study location was chosen as Bali because of the significant lifestyle changes driven by tourism, making it a unique context for examining these phenomena. In this study, the quantitative approach was applied through survey questionnaires among 200 respondents in Denpasar, Bali, using a purposive sampling technique. Data analysis was performed with PLS-SEM to investigate the relationships among the identified psychological factors, consumer behavior, and gadget ownership as a mediating variable. This is a geographically limited study that might affect generalization, but it is of great value to present the emotional and digital determinants of Generation Z's consumption patterns. The following research contributes to understanding the emotional and social media influences of consumer behavior in the digital era by bridging gaps between psychological theories and digital consumption trends.